Optimalisasi Pengelolaan dan Pemanfaatan Lahan Untuk Mendukung Ketahanan Pangan Di Desa Sindangsari Dalam Mewujudkan Visi Integrated, Smart, and Green Campus - Gunawati, Anne; Muslih, Muhamad; Agus, Dede (MADINAH, 2021)
The provision of agricultural land for food is currently facing pressure due to competition from other sectors as a result of economic growth and population growth. This condition causes food agriculture land to be faced with the problem of decreasing land area due to conversion to non-agricultural uses. The converted land area is mostly intended for residential housing developments in addition to the construction of public infrastructure, offices, shops and industries. This conversion of agricultural land can have a negative impact on agricultural development. Each district or city actually has to reserve and protect agricultural land that has the potential to be developed into sustainable food-producing agricultural land. However, in its implementation, the determination of the area for sustainable food-producing agricultural land has not been carried out by many districts or cities for various reasons. Likewise in Banten, the availability of agricultural land in Banten Province is getting depleted due to being eroded by development, new efforts and breakthroughs are needed in maintaining the availability of agricultural products while maintaining food security for the Banten people, one of which is by utilizing idle land owned by developers in urban areas so that they can be worked on by the community. farmer. Currently, the management of idle land owned by developers in urban areas is still not optimal. As a result, a lot of unused land is left empty before being built into housing. There needs to be support from all parties so that the management of unused land can be optimized in maintaining food security in Banten Province can always be maintained, in addition to avoiding consumptive people's habits, relying on all their daily needs from buying, while a lot of land can still be cultivated and cooperated. This study explains about Land Management and Land Use for Food in the area around the Untirta Sindang Sari campus and around the Sindang Sari village area which is still not optimal. This research is also to find out, examine and develop alternative policies related to efforts to optimize the potential of agricultural land used for food utilization. The long-term goal of this research is that this research aims to optimize land use and management to support food security in Banten and national food security. Food products in Banten can not only meet the needs of their own region, but can also meet the needs of National Food and even for export commodities to foreign countries. The specific target to be achieved from this research is to strive to achieve one of Untita's Visions and Missions, namely Realizing the Integrated, Smart, and Green Campus Vision. The Ministry of Education, Culture, Research and Technology (Kemendikbudristek) has made Sultan Ageng Tirtayasa University a Center for the Study of Food Security and Local Food Innovation in Banten so that with the new Untirta Building from the Islamic Development Bank (IsDB), Untirta can become a center of excellence. in Food Security. Untirta does not only focus on the development of food products, but is also accompanied by the development of technology. This research uses Sociological Normative and Juridical Normative legal research methods. This research is descriptive analytical and uses primary data sources and secondary data sources. Descriptive in this study is a description of the situation, conditions, circumstances, and realities that exist in the area around the Untirta Sindang Sari campus and around the Sindang Sari village area in terms of land use and land management to support food security. Then analyze what the problem is in order to find a solution to the problem. Sources of data used in this study were obtained from Library Research (Library Research). The normative juridical in this research is in the form of a discussion of several laws and regulations made by the government that are enforced to regulate the formation of regional areas and land use. Sociological Normative Research on law constructs law as a system of laws and regulations that have existed so far and then constructed in a society's behavior.